The Profiles and Artistic Experiences of Street Musicians in the Urban Spaces of Montpellier, Sète, and Paris - Chorzępa Joanna (Musicology Today)
The figure of the street musician has long attracted much attention among scholars working in various academic disciplines. This paper attempts to answer the question of who the street musician / artist actually is. While on a scholarship to Paul-Valéry Montpellier 3 University in 2013, I conducted a number of surveys and experiments in order better to understand what situations present-day musicians face while playing in the streets and how their social status is changing. Interviews with street performers and their audiences prove to be a valuable source of information. The paper presents the results of my own field research conducted both among street musicians and their audiences, as well as my own personal experience of performing music in public urban spaces in Montpellier, Sète, and Paris